Revitalizing Majelis Krama Desa for the Development of Tourism Villages and the Achievement of SDGs in West Nusa Tenggara - Iqbal, Muhammad; Zul Anwar; M. Ary Irawan; Sa’di, Kholisussa’di; Rila Hardiansyah; Helmi (Transformasi : Jurnal Penelitian dan Pengembangan Pendidikan Non Formal Informal, 2025)
Abstract: This study examines the transformation of traditional customary institutions from conflict mediators into development agents that support village independence through community-based tourism. The focus is on the Majelis Krama Desa (MKD) in West Nusa Tenggara, which has evolved from a reactive dispute resolution body to a proactive institution in community-based development. The research method employed a literature review with a thematic approach, analyzing scientific publications, policy documents, and official reports published between 2015 and 2025. The findings reveal that the transformation of MKD from a conflict resolution institution into a driver of village self-reliance through tourism significantly contributes to the achievement of SDG 8 (Decent Work and Economic Growth), SDG 11 (Sustainable Cities and Communities), and SDG 16 (Peace, Justice, and Strong Institutions). The main challenges include cultural erosion, authority conflicts, and limited institutional capacity. This study recommends strengthening MKD through systematic capacity-building programs and integrating its roles into the Rencana Pembangunan Jangka Menengah Desa (Village Medium-Term Development Plan).